Unilateral vocal cord paralysis secondary to central bronchogenic carcinoma - Reddy Ravikanth (Indian Journal of Medical and Paediatric Oncology)
Vocal cord paralysis may arise from neurogenic paralysis or mechanical fixation. It is sometimes the only sign of an underlying disease. Thus, it is clinically important to diagnose the primary disease in cases of vocal cord paralysis because many of its potential causes, such as symptom-free malignant tumors, can be fatal or cause serious morbidity if detected late. Radiologic evaluation is often useful for determining the etiology of vocal cord paralysis.